Linguistic Polarization and Conflict in the Basque Country - Javier Gardeazabal (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper investigates the relationship between linguistic polarization and conflict in the Basque Country. During the 40 years of Franco's dictatorship the use of the Basque language was banned. Therefore, there may be some linguistic roots underlying the conflict in the Basque Country. We show that at the municipality level, linguistic polarization reduces the level of conflict. This finding is robust to various ways of measuring linguistic and ideological polarization and the inclusion of other covariates. In addition, we find that a high level of the stock of human capital is beneficial for reducing conflict intensity.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330; Linguistic Polarization; Fractionalization; Terrorism; Conflict